THE USE OF JIGSAW TECHNIQUE IN IMPROVING STUDENTS’ ABILITY IN WRITING A DESCRIPTIVE TEXT - Retna Oktaviani Zahra (Journal of English and Education, 2014)
This research was aimed at investigating whether there is any improvement of students’ writing ability in writing a descriptive text by the implementation of Jigsaw technique and discover students’ response to the use of Jigsaw technique in teaching writing descriptive text. This research employed quantitative method in the forms of quasi-experimental design. This quantitative research involved two classes of tenth grade at one senior high school in West Bandung in which one class was assigned as the experimental group and the other one was assigned as the control group. The instruments used were pre-test, post-test, and questionnaire of attitudes towards the Jigsaw technique. The post-test scores of the two groups were compared by using Independent t-test. The results showed the significance value was lower than the significance level which was 0.043 0.05. It meant that the Jigsaw technique improved students’ ability in writing a descriptive text. Based on students’ attitudes toward the use of Jigsaw technique, the findings indicated that most of students rated the used technique moderately positive.  Nearly all of students agreed that Jigsaw technique is able to improve their writing skill, advance their grammatical mastery, increase their vocabulary mastery, expand their creative thinking, and improve their presentation skill as well as their confidence. Keywords: Jigsaw technique, cooperative learning, writing skill